CREDIT OPERATIONS OF COMMERCIAL BANKS AND THEIR INFLUENCE ON BANKING ACTIVITIES - Ibadullayev Shokhboz Tulkun ugli (The Conference Hub, 2025)
Bank loans occupy a high place in the share of assets of commercial banks operating in the Republic of Uzbekistan. Total assets of banks as of August 1, 2025 In their composition, 576.247.0 billion soums, or 67.6% of the total assets, are accounted for by credit operations, amounting to 852.381.0 billion soums[1]. This requires a deep analysis of credit operations and related indicators when studying the activities of commercial banks.As noted by the renowned economist O.I. Lavrushen, "the effectiveness of a bank in the field of lending is a holistic characteristic of it not only economically, but also socially and organizationally. Economic efficiency, in turn, as the core of the entire model, is a qualitative, not a quantitative, result of the bank's activity in the field of lending. Among the most important economic characteristics (indicators) of lending efficiency, it is important to include not only income, but also the growth of capital value, the quality of credit products, etc. Indicators of the economic efficiency of credit activities can be such qualitative indicators as the profitability of bank loans (loans and borrowings), the growth of the market value of bank bonds, and the ratio of the bank's operating expenses to its operating income in lending.Indeed, the above opinion is important for the economy and banking system of the Republic of Uzbekistan. From January 1, 2021, lending to projects within the framework of state programs is carried out primarily through JSC "People's Bank," JSCB "Microcreditbank," and JSCB "Agrobank" at the refinancing rate of the Central Bank of the Republic of Uzbekistan. This represents the social function of bank credit.